Simulation of fixed bed separation kinetics - Tan, Kee Quan. (2010)
The aim of this report is to investigate the fixed bed kinetics using the simulation of breakthrough curves for fixed-bed adsorption columns. The mathematical models used are Thomas solution and Bohart-Adams solution. The solute featured in this study are malachite green (MG) dye and bovine serum albumin (BSA). The adsorbents used are chitosan hydrogels synthesized for these experiments. Simulation of the breakthrough curves were done based on experimental results from the adsorption of the MG and BSA. MG adsorption in a fixed bed column was carried out at the inlet concentration of 10 ppm with varying volumetric flow-rates from 0.97 millilitre per minute to 4.95 ml/min. BSA adsorption was carried out at inlet concentrations of 25 ppm, 50 ppm and 75 ppm concentrations at 3 ml/min and 4 ml/min. The behaviour of MG adsorption on was found to be described well by Thomas solution for all the MG absorption experiments. The behaviour of BSA adsorption was found to require further investigations to describe its adsorption.